The Firewood-Fried Shrimp Crackers MSME: A Model for Sustainable Local Economic Empowerment - Prameswari, Nanda; Pitri, Alisyah; Khoiratun Nisak, Sayida; Nisak Munamah, Anatun; Dewi , Hasna; Kartika Devi, Erwina; Edi Saputra, Ahmad (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to examine the role of the Firewood-Fried Shrimp Cracker Micro, Small, and Medium Enterprise (MSME) in Mendahara Ilir Village, East Tanjung Jabung Regency, in enhancing the income of coastal communities. Employing a qualitative approach with a descriptive method, data were collected through direct observation, in-depth interviews, and documentation, and were subsequently analyzed inductively using data reduction, data display, and conclusion-drawing techniques. The findings indicate that this MSME makes a significant contribution to the local economy by creating employment opportunities for low-educated workers, increasing household income, and improving quality of life in areas such as education, health, and housing. The enterprise’s main strengths lie in production skills inherited across generations and the use of traditional methods that preserve its distinctive flavor. Nonetheless, it faces challenges including limited capital, unstructured management, a shortage of skilled labor, and dependence on raw material supplies affected by weather and environmental conditions. Government support in the form of training, financial assistance, and marketing facilitation has helped expand market reach. The study concludes that, with strengthened managerial capacity, improved access to financing, and the development of adaptive marketing strategies, the Firewood-Fried Shrimp Cracker MSME has the potential to serve as a sustainable model of local wisdom-based economic development